Innovation and Healing in Contemporary Yup’ik Mask Making - Mossolova, Anna (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This ethnographic study, conducted with seven contemporary Yup’ik carvers examines one of the oldest, but long suppressed, art forms in southwest Alaska – mask making. In-depth individual interviews captured the voices of artists of different ages, backgrounds and experiences, who, as they branch out and push the boundaries of traditional media, keep re-exploring and forging their cultural identity by bringing the forgotten symbols, values and worldviews associated with masks back to life. This article demonstrates how innovation unfolds the healing potential of masks and can help individuals and communities recuperate from a colonial past, and assert positive self-identification as Alaska Indigenous peoples today.